The Impact of the Parental Support on Risk Factors in the Process of Gender Affirmation of Transgender and Gender Diverse People - Seibel, Bruna L.; de Brito Silva, Bruno; Fontanari, Anna M. V.; Catelan, Ramiro F.; Bercht, Ana M.; Stucky, Juliana L.; DeSousa, Diogo A.; Cerqueira-Santos, Elder; Nardi, Henrique C.; Koller, Silvia H.; Costa, Angelo B. (Frontiers in Psychology, 2018)
Research involving transgender and gender diverse people (TGD) increased in the last years, mostly concerning healthcare associated to this population. Few studies dedicated their analysis to the impact of parental support on transgender people, even though this is an important aspect in creating a safe environment on which these individuals can build their identity. In addition, the link between family support, TGD identity and homelessness is not completely established. Thus, due to the specificities of the family context of TGD individuals, the aim of this study is to investigate the association between family support and TGD in different moments of the process of gender affirmation. In addition, this study also aims to explore the relationship between a lack of social support and low self-esteem, home abandonment, and dwelling in the street. The survey was designed based on the TransPULSE project and was made available in electronic format. The sample was constituted of 423 TGD residents in two Brazilian states. A Structural Equation Model analysis suggested that the impact of gender affirmation status on homelessness was mediated by parental support, through self-esteem, and the need to move from home. the association between the status of the gender affirmation procedures, family support and self-esteem was significant and indicated that the further TGD individuals advanced in gender affirmation, the more self-esteem and family support they would have. The association between family support and self-esteem indicated that family support was associated with higher self-esteem. Low family support was associated with the willingness to move from home due to one’s TGD status and there was also a significant correlation between low self-esteem and the willingness to move from home due to one’s TGD status. Finally, homelessness was associated with the willingness to move with a large effect size. Limitations include the sample that was constituted by individuals with Internet access and who had more contact with TGD communities. The findings indicate directions for interventions involving TGD people and their families, considering the parental relationship as a critical variable to improve TGD quality of life in the process of gender affirmation.